Effect of different dance training on forced expiratory volume among post pubescent girls - Akeepan, S.; Sabaananth, S. (Gulbarga University, Kalaburagi, Karnataka, India, 2017)
Dance is a low impact exercise which improves respiratory function through the activity is performed in aerobic nature. The aim of this study was to find out the effect of different dance training on Forced expiratory volume (FEV). To achieve the purpose ninety (N=90) women students (mean age 17 ± 1.3 years) were randomly selected from, Jaffna, Sri Lanka as subjects and divided in to Aerobic Dance (AD), Bharathanatyam Dance (BD) and Kandyan Dance (KD) groups. They were practice their respective dance for 60±10min / day for 3 days / week over the period of twelve weeks. Data were collected on Forced expiratory volume (FEV) by PC based USB Spirometer before and after the intervention programme. Dependent ‘t’ test was used to find out the difference between pre and post test. After eliminating the influence of pre-test on post-test means of experimental groups the analysis of variance (ANOVA) was used to find out the mean gain differences. In addition to this, Scheffe’s post-hoc test was employed (p=0.05). The results reveals that, aerobic (Percentage of Improvement (PI) 23.59), bharathanatyam (PI 16.91), kandyan (PI 9.9) dance training significantly (p=0.05) (F= 14.33*) influence the Forced expiratory volume. Further the result of post hoc test showed that there was a significant difference between Aerobic and Bharathanatyam (Mean Gain Difference (CI=0.10) (MGD) 0.11*), Aerobic and Kandyan dance (MGD 0.25*), and Bharathanatyam dance and Kandyan Dance (MGD 0.14*) groups on Forced expiratory volume. From the result it was concluded that aerobic, bharathanatyam and kandyan dance training positively influence on pulmonary function in respect of Forced expiratory volume. Hence it was recommended that, any type of continues exercise positively influence on lung function in respect to forced expiratory volume.
Keywords: Aerobic; Bharathanatyam; FEV; Kandyan dance